Formation Kinetics and Structural Features of Beta‐Amyloid Aggregates by Sedimented Solute NMR. Issue 14 (2nd July 2013) - Bertini, Ivano; Gallo, Gianluca; Korsak, Magdalena; Luchinat, Claudio; Mao, Jiafei; Ravera, Enrico
Abstract The accumulation of soluble toxic beta‐amyloid (Aβ) aggregates is an attractive hypothesis for the role of this peptide in the pathology of Alzheimer's disease. We have introduced sedimentation through ultracentrifugation, either by magic angle spinning (in situ) or preparative ultracentrifuge (ex situ), to immobilize biomolecules and make them amenable for solid‐state NMR studies (SedNMR). In situ SedNMR is used here to address the kinetics of formation of soluble Aβ assemblies by monitoring the disappearance of the monomer and the appearance of the oligomers simultaneously. Ex situ SedNMR allows us to select different oligomeric species and to reveal atomic‐level structural features of soluble Aβ assemblies.